Mulberry leaf polysaccharide alleviates liver damage and glucose metabolism disorder in largemouth bass (Micropterus salmoides) induced by high-starch - Qinqin Xiao; Lele Wei; Lihong Yin; Yimin Jiang; Qianting Zheng; Jiajie Wang; Ting Ye; Yangyan Wang; Tong Zhou; Lingtao Nie; Zhuangwen Mao; Fufa Qu; et al. (Aquaculture Reports)
The present study evaluated the beneficial impact of MLP on liver damage and glucose metabolism disorder which induced by dietary high-starch in largemouth bass (Micropterus salmoides). The diets with 10 % low starch (LS) group and the diet with 20 % high starch (HSM0) were used as the control diet and the other four diets were formulated with supplementation of 2 %, 4 %, 6 %, and 8 % MLP based on the HSM0 diet. Apparent healthy fish were randomly assigned to six groups with each group consisting of three replicates (30 fish per net), and fed for 8 weeks. Collection of blood and liver samples allowed for enzymological, histopathological, ultramicroscopic, and transcriptomic analyses. Results indicated that adding the right amount of MLP to high-starch feed (HSM4) can significantly decrease the hepatopancreas index, serum glucose levels, and muscle glycogen, mitigate severe vacuolation of liver cells induced by high starch, significantly stimulating the enzyme activities of liver hexokinase (HK) and pyruvate kinase (PK), and significantly decreased the activity of gluconeogenesis. Transcriptomic analysis identified most DEGs significantly enriched in the signaling pathways related to glucose metabolism, starch metabolism, and insulin resistance between the HSM0 and HSM4 groups. PI3K/Akt pathway plays a key role in the effectiveness of mulberry leaf polysaccharide in mitigating liver injury caused by high starch in largemouth bass. Gene expression analysis also confirmed the transcriptome findings. MLP can improve the growth performance and liver damage of largemouth bass fed with HS diet, and reduce muscle glycogen accumulation induced by high starch. In addition, the addition of MLP plays a key role in alleviating the effects of dietary high-starch on liver damage in largemouth bass by regulating key enzymes in carbohydrate metabolism and through the PI3K/Akt signaling pathway and insulin resistance.